The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/micr.30136
|View full text |Cite
|
Sign up to set email alerts
|

Double‐paddle peroneal flap for extensive lip defect reconstruction

Abstract: Free double-paddle peroneal flap transfer could augment lip definition, deepen the labial vestibule, and provide an acute-angle oral commissure, leading to satisfactory oral competency and improved cosmetic results. Therefore, this technique may be considered a viable option for extensive lip defect reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Because multiple perforators could be usually found in the lateral lower leg, a double‐paddle peroneal flap could be easily harvested (Yang et al, ). With its relative thinness compared to antero‐lateral thigh flap (Hsu et al, ), the peroneal flaps could be easily reshaped into desirable shapes, such as acute‐angle mouth angle (Liu & Yang, ), hemiglossectomy defect (Lin, Liu, Lin, Chen, & Yang, ), hypopharyngeal defect (Lin et al, ), or extensive lip reconstruction (Lin, Liu, Lin, Chen, Hsueh et al, ). The novelty of this report is that we refine our design to maximize the area of skin paddle we could harvest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because multiple perforators could be usually found in the lateral lower leg, a double‐paddle peroneal flap could be easily harvested (Yang et al, ). With its relative thinness compared to antero‐lateral thigh flap (Hsu et al, ), the peroneal flaps could be easily reshaped into desirable shapes, such as acute‐angle mouth angle (Liu & Yang, ), hemiglossectomy defect (Lin, Liu, Lin, Chen, & Yang, ), hypopharyngeal defect (Lin et al, ), or extensive lip reconstruction (Lin, Liu, Lin, Chen, Hsueh et al, ). The novelty of this report is that we refine our design to maximize the area of skin paddle we could harvest.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we would like to introduce a novel design of using the obliquely‐arranged double skin paddles to maximize the harvested skin area of lateral lower leg. The design can be applied to fibula flap, or peroneal flap which is the boneless version of fibula flap (Lin, Liu, Chen, & Yang, ; Lin, Liu, Lin, Chen, & Yang, ; Lin, Liu, Lin, Chen, Hsueh et al, ; Liu & Yang, ; Wolff, ; Yang, Leung, & Chen, ). Herein, we present a series of eight cases with extensive through and through defects reconstructed with single fibula or peroneal flap.…”
Section: Introductionmentioning
confidence: 99%
“…The peroneal flap is a reliable choice in complex head and neck reconstructive surgeries. [2][3][4][5][6] Issues regarding donor-site morbidity with peroneal flaps compared with other fasciocutaneous flaps, such as the anterolateral thigh flap or RFFF, are constantly debated among reconstructive surgeons. We used a patient-reported questionnaire rather than objective instrumental analysis because patient-reported outcomes can more accurately reveal the level of discomfort and impact of donor-site morbidities on patients' daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…1 At our institute, peroneal flaps (fasciocutaneous or myofasciocutaneous flap) have been standard for reconstructing soft tissue defects after ablative surgery, such as tongue and esophageal defects that require thin and pliable flaps, or through-and-through defects involving the mouth angle and lips that require complex designs and reliable multiple perforators. [2][3][4][5][6] In other institutes, the radial forearm free flap (RFFF) and medial sural artery perforator (MSAP) flap have been alternatives for defects that require a thinner and more pliable flap. However, we prefer the peroneal flap for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The ulnar forearm flap has been described with the advantage of better donor site location and improved aesthetic outcome as compared to the RFF (Hekner et al 2013). The double-paddle peroneal flap is an alternative when the RFF would be too small and can better restore the vermilion-cutaneous junction (Lin et al 2017), while the dorsalis pedis flap has been suggested as a salvage option in select patients (Stathas et al 2014). If persistence of lower lip incompetence is an issue after reconstruction, the use of a double temporalis transfer with fascia lata sling may be an option (Chan et al 2012).…”
Section: Alternative Reconstructive Optionsmentioning
confidence: 99%